Sound power level of road vehicles running on dense asphalt pavement at various sites in Japan - Okada, Yasuaki; Sakamoto, Shinichi; Ichikawa, Tomoki; Uemura, Tomoaki; Yamauchi, Katsuya; Yonemura, Miki; Yoshihisa, Koichi; Lee, Hyojin (Acoustical Science and Technology, 2020)
Road traffic noise is one of the major environmental issues in urban areas. In Japan, the road traffic noise prediction model ``ASJ RTN-Model 2013,'' which has been developed by the Research Committee in the Acoustical Society of Japan (ASJ), is used widely in environmental impact assessment. Several calculation formulas for the A-weighted sound power level, LWA, of each type of road vehicle are specified in this model. Among them, the formulas for LWA of road vehicles on dense asphalt pavement have been derived using the measurement data acquired in 1991–1998. In this study, to improve the accuracy of LWA for dense asphalt pavement, pass-by noise measurements were performed on 40 actual roads during the last decade. The results revealed that LWA of passenger cars, including hybrid vehicles and mini-sized vehicles, was 1.1 dB lower than that adopted in ASJ RTN-Model 2013. Regarding the other vehicle types such as large-sized vehicles, the differences between LWA obtained from field measurements and those in the model were 0.5 dB or less, and no marked changes in LWA were found.